2008
DOI: 10.1002/ajp.20625
|View full text |Cite|
|
Sign up to set email alerts
|

Diet of spider monkeys (Ateles geoffroyi) in Mesoamerica: current knowledge and future directions

Abstract: Here we review all published articles and book chapters, as well as unpublished theses and data of Ateles geoffroyi diet to (1) summarize the literature; (2) synthesize general feeding patterns; (3) document plant taxonomic similarity in diet across study sites; and (4) suggest directions for future research and conservation priorities. We found 22 samples from five countries: Mexico, Guatemala, El Salvador, Costa Rica and Panama. Tropical wet forest is the most studied habitat (N=13 samples), followed by trop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
118
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(126 citation statements)
references
References 72 publications
7
118
0
1
Order By: Relevance
“…This preference has been reported for other Mexican southeastern populations of Ateles (Martínez and GalindoLeal, 2002;Ramos-Fernández and Ayala-Orozco, 2002;González-Zamora et al, 2009;Scherbaum and Estrada, 2013) in common and dominant plant families in tropical forests such as Fabaceae and Moraceae (Primack and Corlett, 2005). The diet of Ateles is mainly based on fleshy fruits and a variable proportion of leaves and blossoms (García-Orduña, 2003).…”
Section: Seed Handlingsupporting
confidence: 72%
See 1 more Smart Citation
“…This preference has been reported for other Mexican southeastern populations of Ateles (Martínez and GalindoLeal, 2002;Ramos-Fernández and Ayala-Orozco, 2002;González-Zamora et al, 2009;Scherbaum and Estrada, 2013) in common and dominant plant families in tropical forests such as Fabaceae and Moraceae (Primack and Corlett, 2005). The diet of Ateles is mainly based on fleshy fruits and a variable proportion of leaves and blossoms (García-Orduña, 2003).…”
Section: Seed Handlingsupporting
confidence: 72%
“…In another study, Morales (2003) observed that monkeys of the genus Ateles based their diet in B. alicastrum in at least 50 %. Previous information has also suggested this relationship because Brosimum is an abundant and wide distributed genus (Russo et al, 2005;Wallace, 2005;Di Fiore et al, 2008;González-Zamora et al, 2009). Likewise, a similar association has been observed, albeit with spatout fruits in Punta Laguna, Yucatán (H. F. Dzul-Cauich, personal observation).…”
Section: Fruit Choice and Seed Handling In Dominant Tree Species In Ymentioning
confidence: 63%
“…This primate is a highly specialized frugivore (González-Zamora et al 2009, Russo et al 2005) that defends stable home ranges, within which the spider monkey concentrate its activities in areas of higher quality (i.e. the so-called 'core areas ';Asensio et al 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…These species account for 57.10 % of the total species producing fruits consumed by peccaries on the ground (Briceño-Méndez et al 2014). Given the importance of their fruits as a source of food, these species have also been described as part of the diet of primates such as the spider monkey, Ateles geoffroyi, and the howler monkey, Alouatta pigra (Hernández-Sarabia 2013), as well as of other ungulates such as the tapir, Tapirus bairdii (O' Farrill et al 2006(O' Farrill et al , 2011 and the temazates deer, Mazama temama and M. pandora (Weber 2008;González-Zamora et al 2009). …”
Section: Methodsmentioning
confidence: 99%